1991
DOI: 10.1017/s0033291700014732
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric assessment of psychiatric disorders in people with learning difficulties (mental handicap): a review of measures

Abstract: SYNOPSISInstruments designed to assess psychiatric disorders in people with learning difficulties (mental handicap) were critically reviewed from a psychometric perspective. Major trends were found in the assessment of psychopathology related to DSM-III and depressive disorders although research in other areas was patchy. Although some psychometrically sophisticated measures were identified the area was characterized by an absence of important psychometric data for many measures. Future research should attend … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 59 publications
0
49
0
1
Order By: Relevance
“…This is an issue that is not unique to the PAS-ADD Checklist; other measures designed to screen for multiple mental health problems amongst people with ID have also been shown to lack specificity in their subscales (e.g. Sturmey & Berman, 1994, for the Reiss Screen; Sturmey et al, 1991, for the PIMRA) or have not reported data on subscale specificity (e.g. the DASH; Matson et al, 1991).…”
Section: The Factor Structure Of the Pas-add 11mentioning
confidence: 99%
“…This is an issue that is not unique to the PAS-ADD Checklist; other measures designed to screen for multiple mental health problems amongst people with ID have also been shown to lack specificity in their subscales (e.g. Sturmey & Berman, 1994, for the Reiss Screen; Sturmey et al, 1991, for the PIMRA) or have not reported data on subscale specificity (e.g. the DASH; Matson et al, 1991).…”
Section: The Factor Structure Of the Pas-add 11mentioning
confidence: 99%
“…Evenhuis, 1992Roeden & Zitman, 1995Evenhuis, 1996;Prasher, 1997;Deb & Braganza, 1999;Burt et al, 1998Burt et al, , 1999Prasher et al, 2002IQCODE Jorm, 1994Schultz et al, 1998 Dementia Scale for Down Syndrome Gedye, 1995Burt et al, 1998Deb & Braganza, 1999;Huxley et al, 2000;Devenny, 2000;Temple et al, 2001 Early signs of dementia checklist Visser et al, 1997Visser et al, 1997Hoekman & Maaskant, 2002 B. Direct assessment of individual Selective reminding test Buschke, 1973Devenny et al, 1996Mini Mental State Exam Folstein et al, 1975Sturmey et al, 1991Nelson et al, 1995;Prasher et al, 1997;Deb & Braganza, 1999;Hon et al, 1999 The DMR was developed as a screening instrument in The Netherlands in the 1980s, and has been evaluated in adults with ID including those with DS. It is widely used in research and clinical practice throughout Europe and the UK.…”
Section: Cognitive Instruments Administered To Informantsmentioning
confidence: 99%
“…Guidelines for the use of these drugs, such as those of the National Institute for Clinical Excellence (NICE, 2001) in the UK, recommend symptom measurement and follow-up of treatment response with tools such as the Mini Mental State Examination (MMSE; Folstein, Folstein & McHugh, 1975), which is also widely used in the general population to screen for dementia. The MMSE has been evaluated in adults with ID, but found to be unsuitable for those with moderate or greater degrees of ID or reading difficulties (Sturmey, Reed & Corbett, 1991). Deb and Braganza (1999) for example, could only apply the MMSE in 55% of their patients.…”
Section: Introductionmentioning
confidence: 99%
“…Research on the psychometric properties of multi-trait assessment and outcome scales with people with intellectual disabilities is generally limited (Aman, 1994;Sturmey, Reed, & Corbett, 1991). The most extensively researched measure is the Psychopathology Instrument for Mentally Retarded Adults (PIMRA) (Senatore, Matson, & Kazdin, 1985).…”
Section: Introductionmentioning
confidence: 99%